DESIGNING OF FUNCTION COMPOSITION LEARNING FUNCTION THROUGH PENDEKATAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Hendra Pratama; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
The function of composition is one of the important material in Mathematics learning because it makes calculation in daily activities easier, for example, in process of book production, metal recycle, change of golden into jewelery, and also in economics, physics, geography and sociology fields. The purpose of this working paper is to describe about enjoyable mathematics learning in composition function material through Pendekatan Pembelajaran Pendidikan matematika Realistik Indonesia (PMRI). In the fact, the students of learning achievement in composition function in class is less satisfy. Most of students get some difficulties to determine about two functions. Therefore, the learning which is able to assist students more interesting in learning and to increase their concept to develop comprehension is needed. This paper will be explain about PMRI which create the students more effective and enjoyable through water bill in mathematics learning such composition function material.